Determination of the Estrogenic Activity of Coffee Extract Solutions Prepared from Capsule Coffee Using the BG1Luc4E2 Assay. (29th May 2020) - Sakaki, Junichi; Melough, Melissa; Yang, Cathy; Provatas, Anthony; Perkins, Christopher; Chun, Ock
Abstract: Objectives: Estrogenic chemicals (ECs) possess estrogenic activity (EA) which can have harmful effects on the reproductive system. Coffee is known to have estrogenic potency due to its natural phytoestrogens, but coffee prepared from plastic capsules (capsule coffee) may increase exposure to ECs and consequently increase EA, potentially increasing risk to reproductive health. The objective of this study was to determine the EA of capsule coffee extract solutions in vitro. Methods: Six varieties of capsule coffee and two varieties of coffee prepared from whole beans using a stainless-steel French press were first brewed then concentrated and extracted. The BG1Luc4E2 assay was then conducted to determine the EA of the coffee extracts. The normalized EA (% RME2) of the coffee extracts was determined as the relative estrogenic potency compared to the maximum normalized EA of the positive control 17β-estradiol (set to 100 % RME2). EA was determined if at least one data point on the concentration-response curve was above 15% RME2 and confirmed via inhibition with the estrogen receptor antagonist ICI 182, 780. The correlation between the EA estimated by the BG1Luc4E2 assay and the estrogenic potential (EEQ) was determined with Spearman's rank correlation coefficient. Results: All eight coffee extract solutions tested positive for EA and results were confirmed by their complete inhibition with ICI. The level of EA for the six capsule coffee extracts ranged from 48 to 56 % RME2, while the level of EA for the two coffee varieties prepared from whole beans were 40 and 42 % RME2. There was a significant correlation between EA and EEQ was (ρ = 0.8857, P = 0.0333). Conclusions: These results indicate that the EAs of capsule coffees were higher than that of coffee prepared from a plastic-free method and that the EA measured in an in vitro model was correlated with the calculated estrogenic potential of the coffee extract's EC contents. Future studies are warranted in in vivo models as well as in humans as tests of estrogenic potency in vitro do not necessarily predict the effects in living organisms. Funding Sources: This study was supported by the National Institutes of Health.